Toxicity of Engineered Nickel Oxide and Cobalt Oxide Nanoparticles to Artemia salina in seawater - Ates, Mehmet (Water Air Soil Pollut, 2016)
In this study, the effects of exposure to engineered nickel oxide (NiO 40–60 nm) and cobalt oxide (CoO <100 nm) nanoparticles (NP) were investigated on Artemia salina. Aggregation and stability of the aqueous NP suspensions were characterized by DLS and TEM. Acute exposure was conducted on nauplii (larvae) in seawater in a concentration range from 0.2 to 50 mg/L NPs for 24 h (short term) and 96 h (long term). The hydrodynamic diameters of NiO and CoO NPs in exposure medium were larger than those estimated by TEM. Accumulation rate of NiO NPs were found to be four times higher than that of CoO NPs under the same experimental conditions. Examinations under phase contrast microscope showed that the nanoparticles accumulated in the intestine of artemia, which increased with increasing exposure concentration. Differences were observed in the extent of dissolution of the NPs in the seawater. The CoO NPs dissolved significantly while NiO NPs were relatively more stable. Oxidative stress induced by the NP suspensions was measured by malondialdehyde assay. Suspensions of NiO NPs caused higher oxidative stress on nauplii than those of CoO NPs. The results imply that CoO and NiO NPs exhibit toxicity on artemia (e.g., zooplankton) that are an important source of food in aquatic food chain.